Amino Acid Ratios In Postinfarction Patients With Type 2 Diabetes Mellitus (Journal of Pharmaceutical Negative Results, 2023)
The aim of the study: to determine serum amino acids as markers and predictors of arrhythmic complications in post-infarction patients with insulin resistance.Materials and methods: 117 patients were examined, who, according to the presence of type 2 diabetes, were divided into two groups: the main group - 85 patients with coronary heart disease with postinfarction cardiosclerosis (PICS) on the background of type 2 diabetes (DM 2) and a comparison group of 32 patients with PICS without carbohydrate metabolism disorders. The median age of the patients was 64.2 years (interquartile range – 60–66.5 years). 21 amino acids (AA) and separate ratios between amino acids competing for entry through the cell membrane were studied. According to Holter ECG monitoring (HMEKG), arrhythmic disorders and heart rate variability (HR and HRV) were determined.Results: A statistically significant decrease in the Tau/Ala index of patients with pathology compared to patients from the control group was determined (p<0.001). At the same time, a more pronounced and reliable decrease was observed in postinfarction patients with insulin resistance. The index was found to be highly specific with a high positive predictive value (PPV).Conclusions: 1. Postinfarction patients with insulin resistance are characterized by a decrease in the Tau/Ala index, which can be one of the potential mechanisms of arrhythmias and insulin resistance. 2. It is advisable to use the Tau/Ala index as a predictor of life-threatening arrhythmias in order to target the targeted therapy of postinfarction patients with insulin resistance. The value of Tau/Ala (<0.038) is advisable to use for the purpose of prescribing therapy and for monitoring the results of treatment of postinfarction patients with insulin resistance.